The role of duration and pitch in signaling quantity in Finnmark North Sámi - Hiovain, Katri; Asikainen, Atte; Šimko, Juraj (10th International Conference on Speech Prosody 2020, 2020)
Ternary quantity opposition is a cross-linguistically extremely rare typological feature. One of the languages using ternary opposition of consonants to signal linguistic contrasts is North Sámi, an endangered language spoken in several countries in the northernmost Scandinavia. Previous studies have shown that while the contrast between the two shorter quantity degrees is phonetically robustly realized using segmental durations, phonetic differences between the two longer degrees are much more subtle and show a considerable regional variation. In this work we investigate other prosodic means that might be used to mark the contrast alongside duration, namely f0 movement and range. We show that the North Sámi speakers that are also native speakers of Norwegian use pitch to co-signal the differences between the two higher quantity degrees, while speakers that are Finnish-North Sámi bilinguals use primarily durational cues. Interpreting these findings in the light of prosodic characteristics of the majority languages (Finnish and Norwegian) we argue that these regional differences reflect the majority language influence which can be a source of the ongoing dialectal divergence, and potential language change. Peer reviewed